The mystery of Hadrian’s missing wreath leaf - Nurpetlian , Jack (KOINON: The International Journal of Classical Numismatic Studies, 2024)
In the process of searching for two-die brockages, a coin of Hadrian was identified with a difference between the obverse relief side and the incuse reverse. A comparison of the two sides clearly shows that it is an ordinary brockage produced from a single obverse die (one-die brockage) with the exception of the outermost wreath leaf missing on the incuse side. A systematic search of other brockage coins of Hadrian revealed more specimens missing an outer wreath leaf. This is not to say that all brockage coins of Hadrian have a missing leaf, which clearly has the outermost leaves despite their proximity to the edge. Consequently, in a systematic, but by no means exhaustive, search through several hundred (online) images of brockage coins depicting wreathed Roman emperors (late 1st c. BC to mid-3rd c. AD), no other similar example was identified. This phenomenon on brockages of Hadrian seems to be more than just a coincidence, since it is hereby known from a few types and specimens of the emperor, hence eliminating the likelihood of it being a one-off ‘fluke’.